Transforming elements to promote neuromanagement: Organizational Challenge (Investigative progress) - Soto-Ortigoza, Maricarmen; Espinosa-Fernández, Eric (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Management has been studied, today exploring concerns in the advancement of styles in times of pandemic, where organizations are observed tarnished by a leader of psychopathic practices known as Neomanagement. The general objective is to analyze the transforming elements to promote Neuromanagement as an organizational challenge. Under a qualitative paradigm, a descriptive, bibliographic methodology was used, with a phenomenological-hermeneutic method, framed in the Bédard model. An in-depth interview applied to 6 informants was designed, as a result alliances and transformation are the crucial business routes to achieve Neuromanagement that concludes with the use of strategy and philosophy.